Resolva as seguintes equações sendo U = Q: 1) 4m – 1 = 7 2) 3m – 9 = 11 3) 3x + 2 + 4x + 9 4) 5m – 2 + 12 = 6m + 4 5) 2b – 6 = 15 6) 2m – 4 + 12 = 3m – 4 + 2 7) 4m – 7 = 2m – 8 8) 6m – 4 = 12 – 9m 9) m + 4 – 3m = 4 +12 m 10) 3 + 4m – 9 = 6m – 4 + 12 11)–5 + 3x + 4 – 12 + 9x 12) 3x + 5 - 2 = 2x + 12 13) 3( x + 2}= 15 14) –2m ( -m + 2) = 3 ( 2m + 1) 15) 12m + 3 (m – 1) = -2(m +1) + 12 16) 2 ( x-1) = 0 17) –3 (m +2) = 1 18) 2 ( x + 2 ) = 12 19) m = -3 ( m – 4 ) 20) 2 ( m + 5 ) = -3 ( m – 5 ) 21) –2 ( y + 4 ) = -7+ 9 ( y – 1) 22) 5 ( x – 4) = -4 + 9 ( x – 1) 23) –5 ( x – 4 ) + 4 = 2 ( - 2 x – 2 ) + 9 24) -2 ( m – 5 ) + 3m = - ( m + 2 ) – 7 25) - ( x + 5) – 6 = -9 ( x – 3 ) – 2 26) x - 7 + 2 ( x – 4 ) = -3 ( x + 2 ) – 8 27)
28)
29)
30)
31)
32) 33)
34)
35)
36)
37)
38)
39)
40)
41)
42)
43)
44)
45)
46)
47)
RESPOSTAS 1. { 2 }
2.
3. {1}
23. { 19 }
4. { 6}
24.
42.
25.
43.
7.
26.
44.
8.
27. { 2 }
45.
9.
28.
46.
10. { -7 }
29. { - 3}
47.
11.
30. {- 6}
5. 6. { 10}
31. 12. { 9} 13.
32.
14.
34. IMPOSSÍVEL 35.
15. 36. 16. { 4} 17.
37.
18. {4}
38.
19. { 3 } 20. { 1}
39.
21. 40. 22. 41.